Pengaruh Kapasitas Sumber Daya Manusia, Pemanfaatan Teknologi Informasi, Pengendalian Intern Akuntansi, Dan Pengawasan Keuangan Daerah Terhadap Keterandalan Pelaporan Keuangan Pemerintah Daerah (Studi pada Dinas Pendapatan, Pengelolaan Keuangan dan Aset Daerah Kabupaten Karanganyar) - Setianingrum, Desy (2016)
This research purposes to analysis and test the factors that affect the reliability of financial reporting of local goverment, which are factors that affect the human resource capacity, information technology utilization, accounting intern control, and control of financial report. This research uses quantitative methode with primary data that collecting questionnaire. Population of this research is finance department staff at DPPKAD Karanganyar. Sum samples are 55 respondent. Analysis tool uses validity, reliability, normality, multicolinierity, heteroscedasticity, regression linear, F, t, and coefficient determination test. The results showed that human resource capacity, information technology utilization, accounting intern control, and control of financial report influences to reliability of financial report of local goverment in Karanganyar regency.